2005
DOI: 10.21273/hortsci.40.3.752
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variability in Staminate Flower and Pollen Grain Production of Diploid Watermelons

Abstract: In 1999 and 2000, a total of 27 diploid watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] cultivars and advanced breeding lines (hereafter referred to as cultigens) were evaluated for staminate flower and pollen grain production to assess their potential to serve as pollenizers (pollen source plants) in triploid watermelon production systems. Male reproductive output (staminate flower and pollen production) was quantified during the peak flowering and fruit setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…Factors that could have the most impact on the yield of triploid watermelon production are the quantity and timing of peak production of staminate flowers and vine growth of the pollenizer. Although a cultigen may have higher quantities of staminate flowers per plant compared with other cultigens, the higher number of staminate flowers may not coincide with a high quantity of pollen (Stanghellini and Schultheis, 2005). Freeman et al (2008) found no variability in pollen viability of diploid watermelon pollenizers.…”
Section: Resultsmentioning
confidence: 95%
“…Factors that could have the most impact on the yield of triploid watermelon production are the quantity and timing of peak production of staminate flowers and vine growth of the pollenizer. Although a cultigen may have higher quantities of staminate flowers per plant compared with other cultigens, the higher number of staminate flowers may not coincide with a high quantity of pollen (Stanghellini and Schultheis, 2005). Freeman et al (2008) found no variability in pollen viability of diploid watermelon pollenizers.…”
Section: Resultsmentioning
confidence: 95%
“…Self-pollination has been reported to vary from 23% to 77% over locations in cucumber (Wehner and Jenkins, 1985). A large variability exists in watermelon cultivars for staminate-to-pistillateflower ratio and for pollen production, which might affect the rate of self-pollination (Lesley, 1924;Stanghellini and Schultheis, 2005). However, our results indicated that the mating behavior was similar for 'Allsweet' and 'Mickylee' although they were chosen for their large differences in fruit morphology.…”
Section: Discussionmentioning
confidence: 66%
“…The environment affects pollen flow in cucurbit crops which, in turn, affects the rate of self-or cross-pollination (Gingras et al, 1999;Stanghellini and Schultheis, 2005). Variation in wind velocity, humidity, light intensity, temperature, and other environmental factors over years and locations may influence pollinator behavior and sex expression in watermelon and thus affect the rate of self-pollination (Kalbarczyk, 2009;Robinson and Decker-Walters, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fiacchino and Walters (2003) also reported greater incidence of hollowheart at lower pollenizer-to-triploid ratios. Other studies on 'Crimson Sweet' and 'Fiesta' have reported that there were no significant differences in staminate flower or pollen production between these two cultivars (Stanghellini and Schultheis, 2005 fruit, excessive growth of the reduced number of fruit, or some other reason. Pollenizer seed costs vary greatly so which pollenizer provides the greatest return on the investment needs to be researched.…”
mentioning
confidence: 69%